Implementasi Kebijakan Adiwiyata dalam Pengelolaan Lingkungan Sekolah Menengah Atas Negeri 4 Kupang - Junindi Mandalika Manobe; I Gusti Bagus Arjana; Robertus Se (Syntax Idea, 2021)
This study aims to explain adiwiyata school policy in the management of the school environment of SMA Negeri 4 Kupang. In this study used qualitative descriptive research method. The data analysis tecnic use Data Collection, Data Reduction, Data Display, and Conclusions Drawing/ Verifying. The results showed that adiwiyata school policy applied in the management of the environment of State High School 4 Kupang, namely the change in vision, mission and objectives that are environmentally sound, namely "Achievement, Character, Insightful Imtaq and Science and Technology, and environmentally sound. In addition, in each subject is always associated with environmental issues that are going on. It is supported by requiring teachers and employees to continue to motivate and direct students to develop environmental care attitudes, through learning, devotional work, seminars and socialization and participate in environmental action. In addition, there is a policy to recycle organic and inorganic waste as creativity and also facilitate water treatment well for the management of a clean and healthy school environment, all delivered through direct or indirect appeals (through the appeal board). In supporting the implementation of the Adiwiyata program, the school allocates funds for environmentally based activities, such as for student, extracurricular, environmental action, seminars and socialization